2007
DOI: 10.1177/1087054707311042
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Stimulation for ADHD

Abstract: This study illustrates the importance of a credible control condition of equal duration and intensity in trials of novel treatments. CMA treatment cannot be recommended for combined-type ADHD without learning disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Forty-five records remained after titles and abstracts were screened for clearly irrelevant records. Two coders independently examined the full text of these 45 records, of which 30 met all inclusion criteria and were included in this review (Addison et al, 2012;Ayres, 1977;Bonggat & Hall, 2010;Bumin & Kayihan, 2001;Clark et al, 2008;Cox, Gast, Luscre, & Ayres, 2009;Davis et al, 2013;Devlin, Healy, Leader, & Hughes, 2011;Fallon, Mauer, & Neukirch, 1994;Fazlioglu & Baran, 2008;Hodgetts, Magill-Evans, & Misiaszek, 2011;Humphries, Snider, & McDougall, 1993;Jenkins, Fewell, & Harris, 1983;Leew, Stein, & Gibbard, 2010;Miller, Coll, & Schoen, 2007;Pfeiffer et al, 2011;Pirajev, Tangtrongchitr, Chandarasiri, Paothong, & Sukprasong, 2009;Polatajko, Law, Miller, Schaffer, & Macnab, 1991;Quigley, Peterson, Frieder, & Peterson, 2011;Reichow, Barton, Sewell, Good, & Wolery, 2009;Schaaf et al, 2013;Schilling & Schwartz, 2004 Umeda & Deitz, 2011;Uyanik, Bumin, & Kayihan, 2003;Van Rie & Heflin, 2009;Watling & Dietz, 2007;Wuang, Wang, Huang, & Su, 2009). …”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty-five records remained after titles and abstracts were screened for clearly irrelevant records. Two coders independently examined the full text of these 45 records, of which 30 met all inclusion criteria and were included in this review (Addison et al, 2012;Ayres, 1977;Bonggat & Hall, 2010;Bumin & Kayihan, 2001;Clark et al, 2008;Cox, Gast, Luscre, & Ayres, 2009;Davis et al, 2013;Devlin, Healy, Leader, & Hughes, 2011;Fallon, Mauer, & Neukirch, 1994;Fazlioglu & Baran, 2008;Hodgetts, Magill-Evans, & Misiaszek, 2011;Humphries, Snider, & McDougall, 1993;Jenkins, Fewell, & Harris, 1983;Leew, Stein, & Gibbard, 2010;Miller, Coll, & Schoen, 2007;Pfeiffer et al, 2011;Pirajev, Tangtrongchitr, Chandarasiri, Paothong, & Sukprasong, 2009;Polatajko, Law, Miller, Schaffer, & Macnab, 1991;Quigley, Peterson, Frieder, & Peterson, 2011;Reichow, Barton, Sewell, Good, & Wolery, 2009;Schaaf et al, 2013;Schilling & Schwartz, 2004 Umeda & Deitz, 2011;Uyanik, Bumin, & Kayihan, 2003;Van Rie & Heflin, 2009;Watling & Dietz, 2007;Wuang, Wang, Huang, & Su, 2009). …”
Section: Study Selectionmentioning
confidence: 99%
“…However, sensory-based treatments, which continue to lack empirical support (Lang et al, 2012), have gained popularity and are a common practice, especially by occupational therapists (Parham et al, 2007) and for children with autism spectrum disorder (ASD) (Case- Smith, Weaver, & Fristad, 2014;Green et al, 2006;Olson & Moulton, 2004). This is likely because children with ASD often present with sensory abnormalities (Baranek, David, Poe, Stone, & Watson, 2006;Ben-Sasson et al, 2009;Boyd et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sergeant et al, 2006). Such interaction might be mediated by vestibular contributions to the parasympathetic and sympathetic systems (see Clark et al, 2008 for a extensive explanation). Corroboratively, several studies found a positive effect on attention disorder during vestibular stimulation treatment using motion devices (e.g.…”
Section: Vestibular Stimulation In Neurodevelopmental Disordersmentioning
confidence: 99%
“…Arnold et al, 1985;Bhatara et al, 1981Bhatara et al, , 1978. However, a recent well-controlled study with a relatively large sample of patients concluded that these results were probably due to nonspecific effects, such as experimenter expectancy or attention given to the child, as they found improvement both in the experimental (rotation on a chair) and the control condition (sitting on the chair watching a video and hearing the same noise) (Clark et al, 2008). …”
Section: Vestibular Stimulation In Neurodevelopmental Disordersmentioning
confidence: 99%